Special Issue “Health and Performance Through Sports at All Ages 3.0” - Gianpiero Greco (Journal of Functional Morphology and Kinesiology)
In recent years, the growing attention of the scientific community on the benefits of sport and physical activity for health and performance has generated a significant body of research [...]